IMPLEMENTASI METODE PROTOTYPE PADA SISTEM PAYMENT GATEWAY UNTUK SEPATU KOTAMA - Nadhira Najmi Hendri Lubis; Tantri Hidayati Sinaga (PROGRESS, 2025)
Digital era nowadays, online payment systems have become an essential component in supporting transaction efficiency, especially for enterpreneur such as Toko Sepatu Kotama. The store's current manual payment process causes several issues, including delayed confirmations, risk of data entry errors, and a lack of convenience for customers. Therefore, this study aims to develop a web-based payment gateway system that is secure, efficient, and easy to use. The development method used is the prototype model, which enables iterative processes involving users to ensure that the system meets actual needs. The system is built using the Laravel framework and MySQL, and integrated with Midtrans as the payment service provider. The interface is designed to be responsive for both desktop and mobile devices.Testing using Black Box Testing shows that all main features function properly, including registration, login, order placement, checkout, and payment processing. Admins can also effectively manage products, orders, and sales reports. The system's advantages include real-time payment notifications and direct integration with Midtrans. The system has proven to improve operational efficiency and user convenience. Future development may include automatic shipping tracking, multilingual support, and more diverse payment options such as credit cards and installment plans. It is also recommended to conduct broader user testing to gain more representative feedback from the market.